MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA DALAM MENGUNGKAP SEJARAH PENYIARAN AGAMA BUDDHA DENGAN MEDIA INTERAKTIF DALAM PEMBELAJARAN AGAMA BUDDHA SISWA KELAS VIII SMP NEGERI 2 PEKANBARU - Kaad Kaad (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This classroom action research aims to increase students' interest and motivation in the subjects of class VIII Buddhism inSMP Negeri 2 Pekanbaru. This research is a classroom action research with the research subjects are Class VIII studentswho are Buddhists, amounting to 9 people including 8 men and 1 woman. Techniques for collecting data through written testtechniques. The results showed that the Buddhist learning outcomes of students experiencing improvement in the first cycle ofmeeting 1 obtained an average score of 72.7. At meeting 2 it increased to 77.0. In the second cycle the meeting 1 increased to75.8. And at meeting 2 it increased to 77.8.